Measuring and modeling material properties during high loading rates - Material characterization of A36 steel under high loading rates using the Split Hopkinson Pressure Bar and numerical modeling - Krohn, Frida (My University, 2025)
This thesis aims to evaluate a method for analyzing the high strain rate behavior of A36 steel by combining experimental testing and numerical modeling. Experiments consisting of uniaxial compressive tests and Split Hopkinson Pressure bar tests were performed to cover low and high strain rates. The method’s ability to use low strain rate data to predict high strain rate behavior using the Johnson-Cook material model was evaluated. Numerical modeling and parameter optimization were performed in LS-DYNA and LS-OPT, respectively. The results showed reasonable agreement between the experiments and simulations for hydraulic compressive and Split Hopkinson Pressure Bar tests. Consistently, an explicit strain rate dependency is present throughout the tests, but fluctuations in the Split Hopkinson Pressure Bar data complicated the data analysis. The method has strengths and limitations. While the Johnson-Cook material model effectively models A36 steel at high strain rates, additional refinements in the numerical model and parameter optimization process are needed to obtain a reliable set of parameter values. Improving the reliability of the strain gauge data and introducing striker velocity measurements could elevate future method development. In this thesis, the method chosen to evaluate steel’s high strain rate behavior provides a foundation for further work. Refinements in experimental setup and numerical modeling are necessary to improve the reliability of the results before they can be applied effectively in future studies.
Keywords: Split Hopkinson Pressure Bar; SHPB; A36; Johnson-Cook